2013
DOI: 10.1371/journal.pone.0059921
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acid Induces Endoplasmic Reticulum Stress and Apoptosis of β-cells by Ca2+/Calpain-2 Pathways

Abstract: Dysfunction of β-cells is a major characteristic in the pathogenesis of type 2 diabetes mellitus (T2DM). The combination of obesity and T2DM is associated with elevated plasma free fatty acids (FFAs). However, molecular mechanisms linking FFAs to β-cell dysfunction remain poorly understood. In the present study, we identified that the major endoplasmic reticulum stress (ERS) marker, Grp78 and ERS-induced apoptotic factor, CHOP, were time-dependently increased by exposure of β-TC3 cells to FFA. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 51 publications
1
47
1
Order By: Relevance
“…Calpain activation has been found to be associated with type 2 diabetes and various neuronal diseases including Alzheimers, traumatic brain injury and cerebral ischemia, suggesting that regulation of calpains is crucial for cellular health (23). We discovered that calpain inhibitor III could confer protection against thapsigargin mediated cell death (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Calpain activation has been found to be associated with type 2 diabetes and various neuronal diseases including Alzheimers, traumatic brain injury and cerebral ischemia, suggesting that regulation of calpains is crucial for cellular health (23). We discovered that calpain inhibitor III could confer protection against thapsigargin mediated cell death (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…1A). Previous studies have shown that calpain 2 activation is regulated on the ER membrane and it plays a role in ER stress-induced apoptosis and β cell death (20,(22)(23)(24), which prompted us to study the role of WFS2 in calpain 2 activation.…”
Section: Significancementioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress has been considered one of the factors to lead to diseases through ER stress-induced apoptosis (Cui et al, 2013;Hamamura and Yokota, 2007). In animal knockout models, GADD153 mediates apoptosis induced by ER stress in pancreatic cells and by ischemic stress induced in brain neuronal cells (Oyadomari et al, 2002;Tajiri et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids such as palmitate induce ER stress, whereas unsaturated fatty acids exert protective effects; in INS1 cells, palmitate activated UPR via the PERK and IRE1 pathways, and the effect was prevented by co-treatment with oleate [65]. In bTC3 cells, palmitate activated all three UPR pathways, through store-activated calcium entry [66]. Palmitate also induced ER stress in a human beta cell line [67].…”
Section: Intracellular Mechanisms Of Lipotoxicitymentioning
confidence: 99%